Socio-Cultural Changes In Developing Career Adaptability In Final State Students of Guidance and Counseling of UIN Bukittinggi - Alfi Rahmi; Firman Firman; Riska Ahmad (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2022)
The development of the era of globalization has had an impact on social and cultural changes in society. One of the changes that have an impact on society is career development. The development of the times has had an impact on career choices from simple to more complex. Responding to this development, students need to carry out career adaptability so that they are ready to enter the world of work. This career adaptability includes four aspects, namely Career Concert, Career Control, Career Curiosity, and Career Confidence. The purpose of this study was to see the Level of Career Adaptability in final semester Guidance and Counseling Study Program students. The sampling technique was purposive sampling, namely final year students totaling 83 people. This type of research is descriptive quantitative with technical analysis of percentage data. The results of the study prove that the career adaptability level of final-year students of the Guidance and Counseling Study Program is in a moderate position with a percentage of 90.4% and 9.6% at a low level. In general, the level of Career Adaptability for Guidance and Counseling students includes aspects of Career Concert, Career Control, Career Curiosity, Career Confidence, but there are still behaviors that do not fully reflect the four dimensions of Career Adaptability.